Influence of Salicylic Acid and Gibberellin Spraying on Some Morphological and Physiological Traits of Fenugreek Plant (Trigonell afoenum- gracenum L.) - Basma Adil Qader (Academic Science Journal)
A field experiment was conducted in the winter of 2022-2023 at a field in Baqubah, Diyala Governorate. The purpose was to investigate the effects of salicylic acid spraying on specific morphological and physiological characteristics of fenugreek plants with varying concentrations of GA3. A factorial experiment was conducted using a randomized complete block design with three replications. One element involved spraying three different concentrations of salicylic acid (0, 10, and 20 mg L-1), whereas the other involved spraying three different concentrations of GA3 (0, 50, and 100 mg L-1). Results indicated that spraying fenugreek plants with a concentration of 20 mg L-1 of salicylic acid significantly increased plant height and potassium content in leaves.